The Chinese government's new approach to ownership and financial control of strategic state-owned enterprises - Mikael Mattlin (Bank of Finland, Institute for Economies in Transition (BOFIT), 2007)
This paper reviews recent regulatory and policy changes that affect the Chinese central government's ownership and authority over the capital allocations of strategic state-owned enterprises (SOE).The paper examines the reform of the central government's relationship with key SOEs as a consequence of the establishment of the State Assets Supervision and Administration Commission of the State Council (SASAC) in 2003, the coming introduction of a centralised operating and budgeting system for SOEs, and the government's ongoing re-evaluation of its ownership policy.SASAC appears to have the potential to develop into a major actor in China's domestic capital allocation, with an active role in strategic financing and restructuring of key sectors of the Chinese economy. The data reviewed for this paper strongly suggests that the Chinese central government aims to retain significant ownership control over key SOEs and, by extension, over a major part of the domestic economy.The new operating and budgeting system is set to significantly enhance central government control over SOEs' capital allocation.
URN:NBN:fi:bof-201408071941
Keywords: G32; G38; P26; P31; 330; State-owned enterprises; privatisation; corporate governance; China